The circularity of product-service systems: the role of macro-, meso- and micro-level contextual factors - Kuhl, Carl-Christian; Skipworth, Heather; Bourlakis, Michael; Aktas, Emel (Emerald, 2022)
Purpose: This paper aims to examine the relationships between macro-, meso-, and microlevel contextual factors that enable or inhibit the contribution of Product Service Systems (PSS) to circularity. It is informed by the Natural Resource-Based View (NRBV) and the multi-level perspective as theoretical lenses. Design/methodology/approach: A theory elaboration approach is used through three in-depth case studies of UK and German manufacturers. Case studies provide use- and result-oriented PSS for personal computers, power tools, and wind turbines. Multiple sources of evidence, including 20 semi-structured interviews, company documents, and quantitative data, are triangulated to improve the validity of the results. Findings: Empirical evidence for relationships between macro-, meso-, and micro-level contextual factors show significant barriers to the extending and cycling of resource loops, primarily through maintenance, repairs, and refurbishment. A firm’s environmental awareness has a determining role in the contribution of PSS to circularity. The evidence from two use-oriented PSS reveals different circularity maturity levels. Originality: This research makes three key contributions. Firstly, it elaborates on NRBV by showing that a firm’s environmental awareness determines product stewardship. The type of product stewardship practices depends on the enabling and inhibiting effects of macro- and meso-level factors. Secondly, it shows that use-oriented PSS have different circularity profiles and proposes three circularity maturity levels. Finally, it provides an empirically validated framework of macro-, meso-, and micro-level enablers and barriers and how they interact to enable or inhibit circularity in PSS.
Keywords: Circular economy; product-service system; circular business model; servitisation; multi-level perspective